Des migrants « pas comme les autres ». Ambivalence des représentations sociales des migrants marocains et subsahariens aux îles Canaries - Andrea Gallinal Arias (L’Année du Maghreb)
Since 2020, the Canary Islands have seen a significant increase in irregular arrivals of migrants from the African continent. This situation has given rise to a number of discourses regarding the migrant population, with varying attitudes towards different categories depending on their origins. This article examines the social representations associated with Moroccan and sub-Saharan migrants, the two main groups arriving in the archipelago via this Atlantic migratory route. Through an analysis of a corpus consisting of interviews, press articles and online comments, the article presents the discourses that circulate in Canarian society with regard to migrants and identifies the different types of arguments that justify them. The corpus, processed using textometry software TXM, is analyzed using the CARIN model of welfare deservingness, which makes it possible to assess the degree of legitimacy accorded to each of the two groups with regard to their reception and access to the various social services. The article puts forward the idea that the social representation of Moroccan migrants in Canarian society, which is more negative than that associated with sub-Saharan migrants, is informed by pre-existing symbolic realities in the archipelago linked to historical and diplomatic relations with Morocco. Finally, the reaction of rejection expressed by part of Canary Island society is reinforced by a “crisis management” of the migration phenomenon.